Built to last : a novel - Hahn, Erin (St. Martin's Griffin, 2022)
"Shelby Springfield has spent the last ten years trying to overcome her past, sanding it away like she does the rough spots on the vintage furniture finds she makes over. But as a former child star, it's hard to forget a mediocre pop career, a meltdown widely documented by the paparazzi, and a huge public break with her former co-star Lyle Jessup. It's also hard to forget her other co-star and childhood sweetheart, Cameron Riggs -- the one who got away. Anytime Shelby has called, Cameron has come running... And then he runs right off again to chase stories around the world by making documentaries, too scared to admit what he really wants. But when Lyle stirs the pot, getting the two back in the spotlight with a home renovation show, Cameron can't help but come on board. There's something in it for everyone -- almost. Cameron wants to come home and set down some roots. Shelby wants to prove to the world she's not the messy party girl anymore. And Lyle wants to twist the screws on his two childhood friends who had more chemistry than he could dream of with anyone. Sparks and sawdust fly as Shelby and Cameron film the pilot for "Homemade" and battle Lyle's shenanigans at every turn. Erin Hahn's Built to Last is a sparkling second chance romance about owning what you're worth and fighting for the one who got away"--